2017
DOI: 10.1093/geront/gnx093
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregivers of Older Adults, 1999–2015: Trends in Characteristics, Circumstances, and Role-Related Appraisal

Abstract: Family caregivers' circumstances generally improved during the 16-year period. Results diverge from prevailing concerns regarding the state of family caregiving and demonstrate the importance of longitudinally monitoring trends in late-life family caregiving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
126
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(130 citation statements)
references
References 28 publications
4
126
0
Order By: Relevance
“…From 1999 to 2015, dementia caregivers were significantly less likely to report physical difficulties (from 30% in 1999 to 17% in 2015) and financial difficulties (from 22% in 1999 to 9% in 2015) related to care provision. In addition, use of respite care by dementia caregivers increased substantially (from 13% in 1999 to 27% in 2015) 338 . However, as noted earlier, more work is needed to ensure that interventions for dementia caregivers are available and accessible to those who need them.…”
Section: Caregivingmentioning
confidence: 98%
See 1 more Smart Citation
“…From 1999 to 2015, dementia caregivers were significantly less likely to report physical difficulties (from 30% in 1999 to 17% in 2015) and financial difficulties (from 22% in 1999 to 9% in 2015) related to care provision. In addition, use of respite care by dementia caregivers increased substantially (from 13% in 1999 to 27% in 2015) 338 . However, as noted earlier, more work is needed to ensure that interventions for dementia caregivers are available and accessible to those who need them.…”
Section: Caregivingmentioning
confidence: 98%
“…Caregivers of people with dementia report providing 27 hours more care per month on average (92 hours versus 65 hours) than caregivers of people without dementia 319 . An analysis of national caregiving trends from 1999 to 2015 found that the average hours of care per week increased from 45 in 1999 to 48 in 2015 for dementia caregivers; over the same time period, weekly hours of care decreased for non‐dementia caregivers from 34 to 24 338 …”
Section: Caregivingmentioning
confidence: 99%
“…Nursing home usage among persons with ADRDs may decrease, in part due to the “rebalancing” of US states' long‐term care expenditures away from traditional nursing homes toward community‐based long‐term care services . Thus, use of community‐based long‐term services and supports that address dementia‐specific care needs for both persons living with dementia and their family caregivers will be critical now and into the future . Throughout the disease trajectory, most persons with dementia (PWD) rely heavily on familial support to assist with providing care .…”
mentioning
confidence: 99%
“…Emerging data suggest that while the majority of individuals find caregiving to be a rewarding experience it can also result in hefty physical, emotional and financial strains (SCAN ). As the population ages, the burden of chronic illness rises and the emphasis on community‐based care grows, it is timely that there is an increasing recognition of the role of unpaid or informal caregivers (Wolff et al., ). Moreover, in many countries ravaged by epidemics such as HIV and tuberculosis, caregiving reaches across multiple generations (Ogden, Esim, & Grown, ).…”
mentioning
confidence: 99%